PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN - Mulyadi, Roza (Universitas Serang Raya, 2016)
The objective of this study is to examine the influence of corporate governance mechanism, namely presence of board independent of director and audit committe to firm value with financial performance as intervening variable. This study takes sample from 31 companies in the Indonesian Stock Exchange, which were published in financial report from 2010-2011. The method of analysis of this research used multi regression. The results of this study show that (1) the presence of board independent of director had negative significant influence to financial performance, (2) audit commite had not significant influence to financial performance, (3) the presence of board independent of director and audit commite had significant influence to financial performance, Keywords : corporate governance, the presence of board independent of director, audit commite, financial performance, firm value,